Fabric-Based Electrochemical Glucose Sensor with Integrated Millifluidic Path from a Hydrophobic Batik Wax - Anshori, Isa; Heriawan, Elfrida Vanesa; Suhayat, Putri Yulianti; Wicaksono, Dedy H. B.; Kusumocahyo, Samuel Priyantoro; Satriawan, Ardianto; Shalannanda, Wervyan; Dwiyanti, Latifa; Setianingsih, Casi; Handayani, Murni (Sensors (Basel, Switzerland), 2023)
In recent years, measuring and monitoring analyte concentrations continuously, frequently, and periodically has been a vital necessity for certain individuals. We developed a cotton-based millifluidic fabric-based electrochemical device (mFED) to monitor glucose continuously and evaluate the effects of mechanical deformation on the device’s electrochemical performance. The mFED was fabricated using stencil printing (thick film method) for patterning the electrodes and wax-patterning to make the reaction zone. The analytical performance of the device was carried out using the chronoamperometry method at a detection potential of −0.2 V. The mFED has a linear working range of 0–20 mM of glucose, with LOD and LOQ of 0.98 mM and 3.26 mM. The 3D mFED shows the potential to be integrated as a wearable sensor that can continuously measure glucose under mechanical deformation.